Monitoring brackishwater aquaculture development using multi-spectral satellite data and GIS - a case study near Pichavaram mangroves south-east coast of India - Jayanthi, M. (Indian Journal of Fisheries, 2011)
Satellite data of Landsat TM, IRS 1B LISS II, IRS 1C LISS III and IRS 1D LISS III were used to monitor aquaculture development and its spatial distribution in Cuddalore District, south-east coast of India. Analysis of satellite images using image processing software ERDAS Imagine 9.0 and Geographic Information System (GIS) software Arc GIS 9.0 indicated that the area under aquaculture was 6.91 ha in 1987, gradually increasing to 67.71 ha in 1994, and reaching a maximum of 380.19 ha in 1998. There was a little shrimp culture development (6.14 ha) from 1998 to 2005 because of risk of White Spot Syndrome Virus (WSSV), epizootics and constraints related to social and environmental concerns raised against shrimp farming. Shrimp farms initially started in the marsh areas close to creeks and then moved inland towards agricultural and fallow lands. Farms developed in clusters along the creeks without affecting mangrove reserve forests between 1988 and 2005 and about 177.02 ha agriculture land including 234.25 ha fallow lands were converted for aquaculture farming. Shrimp culture was abandoned in 109.47 ha and 15.13 ha of agricultural land previously converted to aquaculture farms, was reconverted for agriculture. The present study shows that remote sensing data and GIS are useful tools in assessing and monitoring the development of aquaculture for larger areas and suggests that national level planning using multi-spectral satellite data can be used to assess the existing land use and the potential for sustainable use of coastal resources.